2002
DOI: 10.1016/s0735-1097(02)01890-9
|View full text |Cite
|
Sign up to set email alerts
|

Reverse remodeling and enhancedadrenergic reserve from passive externalsupport in experimental dilated heart failure

Abstract: Reverse remodeling with reduced systolic wall stress and improved adrenergic signaling can be achieved by passive external support that does not generate diastolic constriction. This approach may prove useful in the treatment of chronic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 38 publications
5
73
0
2
Order By: Relevance
“…Porcine and ovine models are characterized by predictable infarction sizes and closely mimic ischemic cardiomyopathy in humans. 105,110 Coronary Microembolization Serial left coronary artery microembolization with polystyrene microspheres has been used to induce dilated ischemic cardiomyopathy in dogs [115][116][117] and sheep. 118 -120 Acutely microembolized myocardium exhibits contractile dysfunction with a profound perfusion-contraction mismatch, and localized inflammatory responses and TNF expression, as well.…”
Section: Large-animal Dcm Modelsmentioning
confidence: 99%
“…Porcine and ovine models are characterized by predictable infarction sizes and closely mimic ischemic cardiomyopathy in humans. 105,110 Coronary Microembolization Serial left coronary artery microembolization with polystyrene microspheres has been used to induce dilated ischemic cardiomyopathy in dogs [115][116][117] and sheep. 118 -120 Acutely microembolized myocardium exhibits contractile dysfunction with a profound perfusion-contraction mismatch, and localized inflammatory responses and TNF expression, as well.…”
Section: Large-animal Dcm Modelsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8]20,21 To date, no study has evaluated LV mechanics in restraint or the effect of adjustable restraint. Current ventricular restraint techniques, such as the Acorn Cardiac Support Device (Acorn Cardiovascular, St. Paul, Minn) and the Paracor (Paracor Medical Systems, Sunnyvale, Calif), do not allow for either the quantitative adjustment of restraint level or the measurement of P tm .…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, Saveedra et al found a 19Ϯ4% reduction in LV EDV over 6 months in a canine model of HF that used the Acorn Cardiac Support Device. 8 Other studies in animal models demonstrated prevention rather than reversal of LV dilation. 5,6 In human studies, modest improvements in LV EDV have been found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large animal acute coronary occlusion model can be accomplished via embolization, 129,130 microspheres, 131 balloon, 132 and ligation. [118][119][120] Canine, ovine, and porcine models are described extensively in the literature.…”
Section: Acute Coronary Occlusion Modelsmentioning
confidence: 99%